Unraveling the structural complexity of niobate units in aluminosilicate glasses and glass-ceramics - Cicconi, Maria Rita; Kimura, Koji; Bradtmüller, Henrik; Deng, Hongyi; Kohara, Shinji; Onodera, Yohei; Hayakawa, Tomokatsu; Shimono, Seiya; Hayashi, Koichi; de Ligny, Dominique (Materials Advances, 2025)
Niobium-containing glasses and glass-ceramics play an important role in several technological applications, but our understanding of the structure-property relationships of many Nb-containing compositions is still rudimentary. To address the current limitations, the present contribution reports data from synchrotron high-energy X-ray diffraction data to unravel the structural evolution of niobate entities in alkali-aluminosilicate glasses. The data obtained are compared with complementary Raman and solid-state NMR spectroscopy data to provide a better interpretation of the macroscopic properties of the glasses and their crystallization behavior in terms of the glass structure. The data show that the incorporation of niobium into the glass network (from 0.2 mol% to 10 mol%) causes a rearrangement of the units and induces large modifications, particularly in the medium-range order. Nb5+ is present in all glasses predominantly in the form of 6-coordinated [NbO6] units with rather invariant bond distances around 2.0 Å. This observation correlates well with the 93Nb NMR data showing similarly small changes in the chemical shift values. A contrasting scenario is presented when looking beyond the first coordination sphere, with a particular focus on the A–Nb (A= alkali) and Nb–Nb correlations. Both are strongly dependent on bulk chemistry, which, in turn, is influenced by the availability and nature of charge-compensating alkali ions. The addition of Nb has a relatively minimal effect on Si and Al units, promoting the association of Nb with other Nb species, thereby initiating the formation of a subnetwork of [NbO6] units in a corner shared environment. Both alkali species and Nb5+ ions in the amorphous state tend to favor a structural arrangement very similar to that of the stable crystalline phas